PENGENALAN TEKNIK PEREKRUTAN DALAM SELEKSI KERJA BAGI SISWA/I SMK MUTIARA BANGSA TIGA - Oey Hannes Widjaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Recruitment is a process of finding and attracting applicants who have the expertise to occupy certain positions within an organization. This process is to collect the best candidates as much as possible to choose the best of the best. One of the recruitment methods that is carried out is interviews. Interviews aim to obtain an overview and information about candidates directly through face-to-face talks. Through interviews we are expected to get to know the candidate closer and deeper. Through our PKM from FEB Tarumanagara University, we provide counseling for students of SMK Mutiara Bangsa III which later these students will immediately go to work in the field in public or private company organizations. The problems faced are sometimes these SMK graduates fail at the time of the recruitment process. Here we provide several techniques and strategies to qualify for job recruitment. PKM with the title